Sorne epiphitic lícheas frona the beech forest of Tejera Negra (Guadalajara, Spain) - Burgaz Moreno, Ana Rosa; Burgos, Javier (Botanica Complutensis, 1990)
BURGOs, 3. & BUnhiÁz, A. R. 1990. Sorne epiphytic lichens from the beech forest of Tejera Negra (Guadalajara, Spain). Bot. Cornplutensis 16: 37-45 (in Spanish). Wc present 22 taxa of epiphytic lichens from heech forest of Tejera Negra (Guadalajara, Spain). AII of them are first provincial records and they have also chorological interest for lichenological Spanish flora. Wc underline: Brvoria capíllaris (Ach.) Brodo & Hawksw., Caloplaca cerinella (NyI.) Flag., Coelocaulon crespoe Barreno & Vázquez, f-Iopocenotnvce sc-a/amis (Ach.) Choisy, Letharia vulpina (L.) 1-fue nad Pertusaria coronata (Ach.) Th. Fr.
Keywords: Licheus; chorology; flora; Guadalajara (Spain)